Isolated thrombotic microangiopathy of the small intestine in a patient with atypical hemolytic uremic syndrome – a case report - Nunius, Christoph (BMC Nephrol, 2020)
BACKGROUND: Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by systemic thrombotic microangiopathy (TMA) reflected by hemolysis, anemia, thrombocytopenia and systemic organ injury. The optimal management of aHUS-patients when undergoing kidney transplantation to prevent recurrence in the allograft is eculizumab, an approved recombinant antibody targeting human complement component C5. CASE PRESENTATION: A 39 year-old woman presented with severe abdominal pain, diarrhea and emesis for 3 days. In her past medical history she had experienced an episode of aHUS leading to end stage renal disease (ESRD) in 2007 and a genetic workup revealed a heterozygous mutation in the membrane cofactor protein gene. In 2014 she underwent cadaveric kidney transplantation. Four years later she had to go back on hemodialysis due to allograft failure following a severe systemic cytomegalovirus infection resulting in transplant failure. At presentation she still received calcineurin-inhibitor therapy and reported subfebrile temperatures and pain projecting over the transplant prior to the current symptoms. A contrast enhanced CT-scan of the abdomen revealed inflammatory wall thickening of the small intestine. Diagnostic endoscopy discovered fresh blood in the small intestine without a clear source of bleeding. Histopathology of the small intestine biopsies showed severe thrombotic microangiopathy. Of note, the patient persistently had no signs of systemic hemolysis. Since the TMA of the small intestine was most likely due to aHUS, eculizumab treatment was initiated which abolished the symptoms. CONCLUSION: Here we report a patient with thrombotic microangiopathy with predominant manifestation in a single organ, the small intestine, due to aHUS with absence of systemic signs and symptoms. aHUS patients usually require a secondary trigger for the disease to manifest. In this case, the trigger may be attributed to the dysfunctional renal transplant, which was subsequently explanted. Histology of the explanted kidney showed severe inflammation due to purulent nephritis and signs of cellular rejection. After nephrectomy, we continued eculizumab therapy until the patient completely recovered. No signs of TMA recurred after discontinuation of eculizumab, further supporting the concept of the renal transplant as the main trigger of TMA of the small intestine in our patient.